Techno-economic optimization of grid-connected photovoltaic (PV) and battery systems based on maximum demand reduction (MDRED) modelling in Malaysia - Subramani G.; Ramachandaramurthy V.K.; Sanjeevikumar P.; Holm-Nielsen J.B.; Blaabjerg F.; Zbigniew L.; Kostyla P. (MDPI AG, 2023)
Electric energy storage; Energy conservation; Genetic algorithms; Battery energy storage systems; Electricity tariff; Grid-connected photovoltaic; Industrial consumers; Maximum demand; Net energy; Photovoltaic systems; Solar PVs; Electric batteries